How Effective Is Credit Analysis in New Car Financing? Insights from PT Clipan Finance Indonesia – Bekasi Branch - Waru, A. Putri Djohar Tenri; Sukmawati, Mutiara (Lembaga Penelitian Universitas YARSI, 2025)
The growth of the financing industry in Indonesia has increased the need for effective credit analysis to maintain service quality and manage credit risk. Previous studies mainly emphasize quantitative risk assessment, while limited attention has been given to evaluating the effectiveness of credit analysis procedures at the operational branch level. This study aims to analyze the process and effectiveness of credit analysis procedures for new car financing at PT Clipan Finance Indonesia, Bekasi Branch. The research adopts a descriptive qualitative approach, with data collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings reveal that the credit analysis process involves debtor data collection, field surveys, creditworthiness assessment by credit analysts, and layered managerial approval based on internal policies. During January–May 2025, 83 financing applications were processed, with 67% approved and 33% rejected due to failure to meet eligibility criteria. Overall, the credit analysis procedures were effective in assessing debtor capability and eligibility. However, challenges remain in document verification and interdepartmental coordination. The study suggests strengthening document validation and improving coordination to enhance credit analysis effectiveness